Badanie poczucia subiektywnego związanego z dzieleniem na sylaby wyrazów języka polskiego – podział wieloelementowych grup spółgłoskowych - Śledziński, Daniel (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2018)
This paper presents the results of a preliminary investigation of subjective feelings related to the syllabification of Polish words written in orthographic form. The results are part of a wider study, and the data presented here are limited to polysegmental word-internal consonant clusters. In the author’s previous articles it was noted that some morphological boundaries are perceived as syllable boundaries – particularly boundaries between a prefix and a stem. The words that contain such boundaries were excluded from the investigation. The main goal was to verify whether the phonostatistical properties of consonant clusters influence subjective feelings related to syllabification. The investigated statistical proprieties concern the frequency of occurrence of consonant clusters, and of parts of them at the beginning of words, in the text corpus. Another goal was to verify whether the syllabification based on phonology differs from that based on subjective feelings.